Disability theatre in Australia: a survey and a sector ecology. Issue 3 (3rd July 2017) - Hadley, Bree
ABSTRACT: In this paper, I use an ecologies approach to present reflections on the history of disability and deaf theatre in Australia, in light of the distinctive local policy, industry, and production frameworks that have supported or failed to support its development in particular directions. After tracing and categorising developments in the field to date, I signal specific policy changes in the local landscape and specific impacts these policy changes could have on the way we conceive, categorise, and fund different types of disability theatre in Australia in the years to come.